Hedged performatives in economic speeches in English and Vietnamese - A contrastive analysis - Hoàng, Thảo Thủy.; Nguyễn Văn Long, Dr. (ĐHĐN., 2014)
This research is aimed to investigate the syntactic, semantic and pragmatic aspects of Hedged per formatives in English and Vietnamese in general and in economic speeches in particular. The investigation is based on a corpus of 20 videos about economic speeches. We examined a variety of linguistic devices functioning to create the speaker’s hedges and various structures of nouns, adjectives, verbs and adverbs in both languages. In order to achieve the set goal the study is carried out through a descriptive and qualitative approach. English is chosen as L2 and Vietnamese is chosen as L1. It is based on a theoretical framework of speech act, epistemic modality, cooperative and politeness principles. Besides, the study also considered the semantic features of hedge performatives according to economic speeches which was divided into four kinds of syntactic structures mentioned above. Then they were used to discover the semantics and pragmatics of hedged performatives under framework of epistemic modality, and politeness speeches. In addition, the research help Vietnamese learners of English use hedged per formatives effectively in their particular communication situations.
Master thesis in social sciences and humanities.
Keywords: economic speeches in English and Vietnamese; economic speeche -- contrastive analysis